Some Aspects of D. Uznadze’s Concept of Objectification - Nadareishvili , Vakhtang (Georgian Psychological Journal, 2022)
When D. Uznadze’s Theory of Set is viewed from the perspective of formation stages, the Theory of Set, per se, and objectification theory are distinguished from each other. In general, theory of objectification aims to explain participation of conscious processes in the formation and functioning of unconscious set and the role of unconscious set in the formation and functioning of conscious processes. Such a perspective implies that the theory of unconscious set and the theory of objectification are two indispensable constituents of an integrate, general psychological Theory of Set. The given article attempts to prove once again the appropriacy of like approach and further elaborate on objectification as a main category of Theory of Set.